Transculturality through Industrial Space: Cembengan at the Colomadu Sugar Factory - Fajarwati, Ade Ariyani Sari; Kurnia, Lilawati (Bina Nusantara University, 2021)
The research aimed to explain Cembengan celebrations held at the Colomadu sugar factory, Karanganyar which was built in 1861. This celebration was held every time the factory would start milled processing sugar cane into sugar. The word â€œcembengâ€ itself came from the Chinese word â€œCengbengâ€, which was a ritual to commemorate deceased ancestors. Cengbeng was held every April 5th by cleaning graves and placing food and prayer tools such as incense and candles. Meanwhile, the Cembengan tradition itself as a ritual also commemorated the ancestors, but its function had turned into a ritual to start the production process at a sugar factory. This ritual was considered important so that it was carried out continuously for hundreds of years in a Javanese industrial space. This ritual was also attended by Dutch officials when it was still under the control of the Dutch East Indies. The research investigated the intersection between space, capital, and culture, which formed an â€˜invented traditionâ€™. The method used was through historicity approach and analyzed the relationship between space and the formation of Cembengan tradition in the Colomadu sugar factory. The results show that the transcultural aspect no longer consults the origin but rather cultural practices that merge cultural boundaries.